All-Inside Anterior Cruciate Ligament Reconstruction Using an Anterior Half of the Peroneus Longus Tendon Autograft. Issue 6 (15th June 2021) - Bi, Mingguang; Zhao, Chen; Zhang, Qiong; Cao, Li; Chen, Xinji; Kong, Mingxiang; Bi, Qing
Background: The peroneus longus tendon (PLT) has been used as a graft in many orthopaedic surgical procedures because of its comparable biomechanical strength with the native anterior cruciate ligament (ACL). Despite its potential, few studies have been performed to investigate the clinical reliability of ACL reconstruction using a PLT autograft. Purpose: To assess the clinical outcomes and donor-site morbidity of ACL reconstruction using an anterior half of the PLT (AHPLT) autograft in patients with an isolated ACL injury. Study Design: Case series; Level of evidence, 4. Methods: Between January 2016 and January 2017, a total of 21 patients with an isolated ACL injury underwent all-inside single-bundle ACL reconstruction using an AHPLT autograft. Knee stability was assessed using the Lachman test, pivot-shift test, and KT-2000 arthrometer (side-to-side difference) with 134-N anterior force and at 30° of knee flexion. Knee function was evaluated using the International Knee Documentation Committee score, Lysholm score, and Tegner score. Donor-site morbidity was assessed using ankle eversion and plantarflexion strength as well as the American Orthopaedic Foot & Ankle Society scoring system and the Foot and Ankle Disability Index. Results: At a mean final follow-up of 40.1 months (range, 36-48 months), the KT-2000 arthrometer side-to-side difference was significantly lower compared with preoperatively (1.1 ± 0.62 vs 7.0 ± 2.18 mm, respectively; P < .001). The mean preoperative International Knee Documentation Committee, Lysholm, and Tegner scores were 52.0 ± 8.27, 50.9 ± 8.50, and 1.8 ± 0.87, respectively, increasing significantly to 94.2 ± 2.61, 95.2 ± 2.64, and 6.8 ± 1.50, respectively, at final follow-up ( P < .001 for all). All patients had grade 5 muscle strength in ankle eversion and plantarflexion at the donor site, with mean American Orthopaedic Foot & Ankle Society and Foot and Ankle Disability Index scores of 96.8 and 97.6, respectively. No complications or reoperations occurred. Conclusion: All-inside ACL reconstruction using an AHPLT autograft produced good functional scores and stability without obvious ankle-site morbidity.